Rice Na+ absorption mediated by OsHKT2;1 affected Cs+ translocation from root to shoot under low K+ environments - Kanno, Satomi; Fujimura, Shigeto; Takahashi, Junko; Li, Chenyu; Shinano, Takuro; Nakamura, Shin-ichi; Leonhardt, Nathalie; Furukawa, Jun (Frontiers in Plant Science, 2024)
137Cs diffused into the environment due to a nuclear power plant accident has caused serious problems for safe crop production. In plants, Cs+ is similar in its ionic form to K+. Cs+ is absorbed and transported mainly by the K+ transport mechanism. However, the full picture of the genes contributing to Cs+ transport and the transport mechanism of rice is still unclear. This study focused on OsHKT2;1, a candidate Cs+ transporter under low K+ conditions. To verify the ability of OsHKT2;1 to transport Cs+, the OsHKT2;1 mutant (hkt2;1) was grown in a 137Cs-contaminated paddy field in Fukushima. The 137Cs concentration in hkt2;1 aboveground was higher than in the wild type (WT), and the K concentration in these samples did not change between WT and hkt2;1, whereas the Na concentration was lower in hkt2;1. Uptake experiments with radioactive tracers (22Na+, 43K+, and 137Cs+) in hydroponic systems with different elemental compositions showed a negative correlation between Na+ and Cs+ accumulation in rice shoot cultivated under low K+ conditions. These results indicated that OsHKT2;1 does not directly contribute to Cs+ uptake but is an important factor in regulating Cs+ translocation by controlling Na+ accumulation. This indicates the possibility of controlling rice Cs content by regulating the Na+ environment during cultivation.